FORMULATION OF NIOSOMAL GEL CONTAINING GREEN TEA EXTRACT (CAMELLIA SINENSIS L. KUNTZE) USING THIN-LAYER HYDRATION - Isnan, Astrid Permatasari; Jufri, Mahdi (International Journal of Applied Pharmaceutics, 2017)
Objective: Green tea is known as a source of antioxidants. The most abundant of these is epigallocatechin gallate, which has been shown to modulate biochemical pathways in the skin. Niosomes are an alternative to liposomal drug-vehicle systems, which have disadvantages such as cost and stability. To overcome the problem of low permeation of active substances through skin layers and to increase their stability, a topical antioxidant preparation based on niosomes was prepared. Materials and Methods: To enhance drug stability, niosomal formulations were prepared in four different molar ratios of surfactant-to-cholesterol, that is, 3:1 (F1), 2:1 (F2), 1:1 (F3), and 0.5:1 (F4). These were prepared using the thin-layer method. The niosomal suspensions were evaluated for particle size and distribution, lamellarity, encapsulation efficiency, and zeta potential, and were then incorporated into gels using hydroxypropyl methylcellulose as the gelling agent. The niosomal gels were evaluated for organoleptic properties, pH, viscosity, stability, and antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl. Results: Results for the suspensions showed that F1 had the best encapsulation efficiency but experienced separation after 7 days. Conclusions: Results for the niosomal gels (using F3) showed stable formulation without changes.